The fisheries potential of Marcusenius pongolensis, Oreochromis mossambicus and Schilbe intermedius in Mnjoli dam, Swaziland - Khumalo, Nokuthula (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2006)
This thesis investigates aspects of the diversity, abundance and biology of the fish species inhabiting Mnjoli Dam, an irrigation dam that is located in the rural lowveld region of Swaziland. Specific objectives for this thesis were: to determine the fish species present and select three principal species based on their abundance; to investigate the relative abundance and distribution of the three selected species; and to describe key population parameters, such as growth, maturity, reproductive seasonality and mortality. The three dominant species were selected on their fisheries potential. These were Marcusenius pongolensis, Oreochromis mossambicus and Schilbe intermedius. Marcusenius pongolensis was the most abundant species in terms of both catch per unit effort and mass. Catch rates were shown to vary according to habitat type. Age and growth parameters were obtained from sectioned otoliths. Marginal zone analysis showed that annulus formation occurred in winter for all three species. The maximum-recorded ages were 8, 6 and 8 for M. pongolensis, O. mossambicus and S. intermedius, respectively. Growth for the three species was best described by the three parameter von Bertalanffy growth model as Lt = 1.88.67(1- expâ »Â¹Â·â ´â ¸â ½tâ ºÂ°Â·â ¶â ·â ¾) mm FL for M. pongolensis; Lt = 226.83(1- expâ »Â°Â·â ´â ½tâ ºÂ²Â·Â°Â²â ¾) mm TL for O. mossambicus and Lt = 214.59(1- expâ »Â°Â·â ¶Â°â ½tâ ºÂ¹Â·Â²Â°â ¾) mm FL for S. intermedius. Sexual maturity was estimated for male and female M. pongolensis at 134 mm FL and 119 mm FL, respectively. Oreochromis mossambicus matured at 239 mm TL and S. intermedius at 205 mm FL. Two spawning peaks for M. pongolensis and S. intermedius were observed, one at the onset of summer (November) and the second at the beginning of autumn (February-March). Oreochromis mossambicus also exhibited two spawning peaks, one in spring (September) and the second in autumn (February "“March). Mean mortality rate (Z), estimated using catch curve analysis was 0.77 yearâ »Â¹ for M. pongolensis, 0.49 yearâ »Â¹ for O. mossambicus and 0.79 yearâ »Â¹ for S. intermedius. Natural mortality was assumed to be equal to Z since there is no fishery activity at the dam. Size specific selectivity curves were developed for each species. Of all the mesh sizes used, the 44 mm mesh size net had the highest catch rates in terms of numbers for M. pongolensis and S. intermedius. The 75mm mesh caught the highest catch rates for O. mossambicus. . The 44mm and 75 mm meshes seem to be the most suitable mesh sizes for harvesting the candidate species. It is concluded that no commercial fishery should be established on the dam, yet a small subsistence fishery could be a possible option. Management options such as input controls, open and closed seasons and areas and minimum sizes are discussed.
Keywords: Mozambique tilapia; Marcusenius pongolensis; Schilbe intermedius; Fishes -- Swaziland; Fisheries -- Swaziland; Tilapia -- Swaziland